Implementasi Kebijakan Perizinan Penimbunan Lahan di Kawasan Hutan Mangrove Kota Tanjungpinang - Suryanti Nengsih, Neng; Sujono, Agus; Kurniadi, Randa (STISIPOL Raja Haji, 2023)
The existence of mangrove forests (mangroves) in Tanjungpinang is threatened with extinction. Little by little the mangrove area began to decrease and start to shrink. Whereas mangrove forests have very important functions and benefits for the ecosystem, water and the surrounding environment. Therefore it is necessary to implement a permit policy for landfilling in mangrove forest areas in order to provide planning, utilization, control, maintenance, supervision and law enforcement. The purpose of this study was to determine the implementation of the permit policy for land hoarding in the mangrove forest area of ??Tanjungpinang City, and to find out what factors were hindering this implementation. This type of research is descriptive with a qualitative approach. Informants in this study are tourism managers, visitors and the government. The data used are primary data obtained through interviews and observation, as well as secondary data through documentation studies. The data obtained were analyzed qualitatively. The results of this study are that the permit policy for landfilling in the mangrove forest area has been implemented, but it is not optimal, due to overlapping policies between existing agencies and causing ambiguity for the community about which policies to follow.